Respiratory muscle strength training and neuromuscular electrical stimulation in subacute dysphagic stroke patients: a randomized controlled trial. (June 2017) - Guillén-Solà, Anna; Messagi Sartor, Monique; Bofill Soler, Neus; Duarte, Esther; Barrera, Mª Camelia; Marco, Ester
Objective: To evaluate the effectiveness of inspiratory/expiratory muscle training (IEMT) and neuromuscular electrical stimulation (NMES) to improve dysphagia in stroke. Design: Prospective, single-blind, randomized-controlled trial. Setting: Tertiary public hospital. Subjects: Sixty-two patients with dysphagia were randomly assigned to standard swallow therapy (SST) (Group I, controls, n =21), SST+ IEMT (Group II, n =21) or SST+ sham IEMT+ NMES (Group III, n =20). Interventions: All patients followed a 3-week standard multidisciplinary rehabilitation program of SST and speech therapy. The SST+IEMT group's muscle training consisted of 5 sets/10 repetitions, twice-daily, 5 days/week. Group III's sham IEMT required no effort; NMES consisted of 40-minute sessions, 5 days/week, at 80Hz. Main outcomes: Dysphagia severity, assessed by Penetration-Aspiration Scale, and respiratory muscle strength (maximal inspiratory and expiratory pressures) at the end of intervention and 3-month follow-up. Results: Maximal respiratory pressures were most improved in Group II: treatment effect was 12.9 (95% confidence interval 4.5-21.2) and 19.3 (95% confidence interval 8.5-30.3) for maximal inspiratory and expiratory pressures, respectively. Swallowing security signs were improved in Groups II and III at the end of intervention. No differences in Penetration-Aspiration Scale or respiratory complications were detected between the 3 groups at 3-month follow-up. Conclusion: Adding IEMT to SST was an effective, feasible, and safe approach that improved respiratory muscle strength. Both IEMT and NMES were associated with improvement in pharyngeal swallowing security signs at the end of the intervention, but the effect did not persist at 3-month follow-up and no differences in respiratory complications were detected between treatment groups and controls.